Suppression of Transmembrane Tumor Necrosis Factor Alpha Processing by a Specific Antibody Protects Against Colitis-Associated Cancer - Ba, Hongping; Jiang, Rui; Zhang, Meng; Yin, Bingjiao; Wang, Jing; Li, Zhuoya; Li, Baihua; Zhou, Xiaoxi (Frontiers in Immunology, 2021)
Soluble tumor necrosis factor-α (sTNF-α) plays an important role in colitis-associated cancer (CAC); however, little is known about transmembrane TNF-α (tmTNF-α). Here, we observed an increase in sTNF-α mainly in colitis tissues from an azoxymethane/dextran sodium sulfate (DSS)-induced CAC mouse model whereas tmTNF-α levels were chiefly increased on epithelial cells at the tumor stage. The ratio of intracolonic tmTNF-α/sTNF-α was negatively correlated with the levels of pro-inflammatory mediators (IL-1β, IL-6 and NO) and M1 macrophages but positively correlated with the infiltration of myeloid-derived suppressor cells, regulatory T cells and the level of the anti-inflammatory cytokine IL-10, suggesting an anti-inflammatory effect of tmTNF-α. This effect of tmTNF-α was confirmed again by the induction of resistance to LPS in colonic epithelial cell lines NCM460 and HCoEpiC through the addition of exogenous tmTNF-α or transfection of the tmTNF-α leading sequence that lacks the extracellular segment but retains the intracellular domain of tmTNF-α. A tmTNF-α antibody was used to block tmTNF-α shedding after the first or second round of inflammation induction by DSS drinking to shift the time window of tmTNF-α expression ahead to the inflammation stage. Antibody treatment significantly alleviated inflammation and suppressed subsequent adenoma formation, accompanied by increased apoptosis. An antitumor effect was also observed when the antibody was administered at the malignant phase of CAC. Our results reveal tmTNF-α as a novel molecular marker for malignant transformation in CAC and provide a new insight into blocking the pathological process by targeting tmTNF-α processing.